2019
DOI: 10.1111/petr.13624
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten‐age neurocognitive, functional, and quality‐of‐life outcomes after liver transplantation at under 6 years of age

Abstract: Background We aimed to describe school‐entry age neurocognitive, functional, and HRQL outcomes and their predictors after liver transplant done at age <6 years. Methods A prospective cohort of all (n = 69) children surviving liver transplant from 1999 to 2014 were assessed at age 55.4 (SD 7.2) months and 38.6 (12.4) months after transplant. Assessment included: the Wechsler Preschool and Primary Scales of Intelligence, Beery‐Buktenica Developmental Test of VMI, Adaptive Behavior Assessment System caregiver‐com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This compared with physical health and psychosocial health summary scores of 74.4 and 73.0, respectively, observed amongst children with BPD in our study (descriptive analyses). Although it is not straightforward to compare and contrast our PedsQL GCS score findings with those in other studies and with ‘population’ norms, a study conducted in Canada [ 42 ] for liver transplant children aged under 6 found that healthy children had a mean total PedsQL score of 82, compared to 73 and 75 for chronically ill children and liver transplant children, respectively.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This compared with physical health and psychosocial health summary scores of 74.4 and 73.0, respectively, observed amongst children with BPD in our study (descriptive analyses). Although it is not straightforward to compare and contrast our PedsQL GCS score findings with those in other studies and with ‘population’ norms, a study conducted in Canada [ 42 ] for liver transplant children aged under 6 found that healthy children had a mean total PedsQL score of 82, compared to 73 and 75 for chronically ill children and liver transplant children, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Amongst these studies, a US study [ 43 ] that estimated PedsQL GCS scores of 20,031 families with children aged 2–16 years showed that healthy children had a mean total PedsQL GCS score of 84, compared to 74 for chronically ill children. Furthermore, as noted above, a Canadian study [ 42 ] of liver transplant children aged under 6 years found that healthy children had a mean total PedsQL GCS score of 82, compared to 73 and 75 for chronically ill children and liver transplant children, respectively.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, childhood represents a vulnerable developmental period. Research has identified a high prevalence of trauma within the pediatric transplant field, 47,48 as well as a high prevalence of neuropsychological issues among pediatric SOT patients when compared to population norms 49–51 . While such findings might point to considerable risk factors of transplantation on long‐term QoL, they might also be capturing deleterious impacts of the underlying disease, which may further justify the benefits of early transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified a high prevalence of trauma within the pediatric transplant field, 47,48 as well as a high prevalence of neuropsychological issues among pediatric SOT patients when compared to population norms. [49][50][51] While such findings might point to considerable risk factors of transplantation on long-term QoL, they might also be capturing deleterious impacts of the underlying disease, which may further justify the benefits of early transplantation. Moreover, it is important to note that the rate of organ re-transplantation in adult patients, who are often transplanted in childhood, is high, 52 which may partially explain findings of older age at assessment and longer time since transplant to be associated with poorer overall QoL.…”
Section: Discussionmentioning
confidence: 99%